(untitled) (Revista de Ciências Agroveterinárias, 2019)
This study aims to present an independent evaluation of the potential of a digital elevation model (DEM/SC), generated by aerophotogrammetry, for applications requiring detailed datasets in the state of Santa Catarina. A total of 20 control points were collected and compared with elevation values derived from DEM/SC, SRTM v.4.1 and TOPODATA according to PEC-PCD. The DEM/SC met the requirements for the 1:10,000 scale in class C, while the DEM SRTM v.4.1 and TOPODATA fitted with the scale 1:50,000 classes A and B, respectively. The DEM/SC classification is consistent with that informed in the aerial survey report. Therefore, one recommends using the DEM/SC in studies and surveys that require detailed elevation datasets in the state of Santa Catarina.